2005
DOI: 10.1111/j.1461-0248.2005.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Why are birds’ eggs speckled?

Abstract: Birds are unique in laying eggs with pigmented shells, but for most species (e.g. most passerines, which lay white eggs speckled with reddish spots of protoporphyrin) the pigmentsÕ function is unknown. We studied a bird population at a geologically variable site, and considered a hitherto untested hypothesis: that protoporphyrin pigments might compensate for reduced eggshell-thickness (caused partly by calcium deficiency), which is known to reduce eggshell-strength and increase eggshell-permeability. We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

18
351
6
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(376 citation statements)
references
References 25 publications
18
351
6
1
Order By: Relevance
“…Recently, it has been proposed that blue and green egg colours may function as a post-mating sexually selected signal of female phenotypic quality to their mates in order to induce a higher allocation of paternal care (Moreno & Osorno 2003). Finally, Gosler et al (2005) have proposed that egg speckling caused by protoporphyrin pigments might compensate for reduced eggshell-thickness due to calcium deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been proposed that blue and green egg colours may function as a post-mating sexually selected signal of female phenotypic quality to their mates in order to induce a higher allocation of paternal care (Moreno & Osorno 2003). Finally, Gosler et al (2005) have proposed that egg speckling caused by protoporphyrin pigments might compensate for reduced eggshell-thickness due to calcium deficiency.…”
Section: Introductionmentioning
confidence: 99%
“…In additon, the Great Tit has no brood parasites, and birds do not eject distinct-looking eggs (Kempenaers et al 1995, R. Hargitai personal observation). In a previous study, we showed that the distribution of eggshell spots was related to eggshell thickness in our Great Tit population (Hargitai et al 2013), suggesting a structural function of shell pigmentation (Solomon 1997, Gosler et al 2005, but the intensity and size of spots were not related to eggshell thickness (Hargitai et al 2013). In this study, we first tested whether eggshell spotting pattern was related to female characteristics that may indicate condition and state of health (body condition, body size, plasma oxidative status, plasma leukocyte count, and clutch size).…”
Section: Introductionmentioning
confidence: 99%
“…Several hypotheses have been proposed to explain the pigmentation of bird eggshells (Kilner 2006, Reynolds et al 2009, Maurer et al 2011a); these hypotheses may not be mutually exclusive and could share similar predictions. Protoporphyrin-based eggshell pigmentation may promote camouflage (Stoddard et al 2011, Lovell et al 2013; it may enhance egg mimicry or permit egg recognition in species exposed to brood parasites (Stokke et al 1999, Soler et al 2000, Moskát et al 2008; it may help resist bacterial penetration into the egg (Ishikawa et al 2010, Fargallo et al 2014; or it may structurally strengthen eggshells (Gosler et al 2005, García-Navas et al 2010, Bulla et al 2012, Hargitai et al 2013, the latter of which is possibly the most plausible explanation for shell spotting patterns in cavity-nesting birds (Solomon 1997, Cherry andGosler 2010). Furthermore, Moreno and Osorno (2003) proposed that eggshell color could be a sexually selected signal, which may advertise the quality of the female and that of her offspring to the male parent in order that he contribute more to the breeding attempt (sexually selected eggshell coloration [SSEC] hypothesis).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations